The dietary paradox in food allergy: yesterday's mistakes, today's evidence and lessons for tomorrow. - Badina, Laura; Barbi, Egidio; Berti, Irene; Radillo, Oriano; Matarazzo, Lorenza; Ventura, Alessandro; Longo, Giorgio (Curr Pharm Des, 2012)
During the last decades the prevalence of food allergy has significantly increased among children and antigen avoidance still remains the standard care for the management of this condition. Most reactions are IgE-mediated with a high risk of anaphylaxis requiring emergency medications in case of inadvertent ingestion. Recent studies showed that continuous administration of the offending food, rather than an elimination diet, could promote the development and maintenance of oral tolerance. Indeed, intestinal transit of food proteins and their interaction with gut-associated lymphoid tissue (GALT) is the essential prerequisite for oral tolerance. On the contrary, low-dose cutaneous exposure to environmental foods in children with atopic dermatitis and altered skin barrier facilitates allergic sensitization. The timing and the amount of cutaneous and oral exposure determine whether a child will have allergy or tolerance. Furthermore, previous preventive strategies such as the elimination diet during pregnancy and breastfeeding, prolonged exclusive breastfeeding and delayed weaning to solid foods did not succeed in preventing the development of food allergy. On the other hand, there could be an early narrow window of immunological opportunity to expose children to allergenic foods and induce natural tolerance. Finally, the gradual exposure to the offending food through special protocols of specific oral tolerance induction (SOTI) may be a promising approach to a proactive treatment of food allergy.
Keywords: Anaphylaxis; Antigens; Breast Feeding; Child; Dermatitis, Atopic; Female; Food Hypersensitivity; Humans; Immunoglobulin E; Pregnancy; Time Factors